Multi-Omics Characterization of a KIF1C Structural Variant in a Patient with a Complex Movement Disorder Partially Responsive to Deep Brain Stimulation - Mirja Thomsen; Max Borsche; Vicente A. Yépez; Dirk Rasche; Kristian K. Ullrich; Vera Tadic; Saad M. Abdelwakeel; Hauke Busch; Sören Franzenburg; Joanne Trinh; Christine Klein; Katja Lohmann; et al. (The Cerebellum, 2026)
Biallelic KIF1C variants are associated with a spectrum of neurological phenotypes, including spasticity, cerebellar ataxia, chorea, and dystonia. Most reported patients involve single-nucleotide variants, whereas copy number variants (CNVs) have been described only once in the PubMed-listed literature. The therapeutic potential of deep-brain stimulation (DBS) in KIF1C -related disease has not yet been evaluated. We report a patient presenting with spasticity, ataxia, dystonia, and head tremor, in whom prior exome sequencing was inconclusive. A multi-omics approach was applied, including optical genome mapping (OGM), genome sequencing, and transcriptome sequencing. The clinical effect of DBS was assessed. OGM revealed a homozygous KIF1C Exon 17–18 deletion, retrospectively detectable in exome and genome data but initially missed by sequence analysis. Transcriptome sequencing demonstrated significantly reduced KIF1C expression and absence of normally spliced transcripts around those exons, consistent with a loss-of-function mechanism. DBS led to partial clinical improvement, with notable reduction of dystonia and head tremor. Structural variants may be an underrecognized cause of complex movement disorders involving spasticity, ataxia, and dystonia. Diagnostic methods specifically targeting structural variation, such as OGM or CNV analysis of short-read data, can be essential for diagnosis. Transcriptome data add valuable functional insight. This report also suggests that DBS may offer symptomatic benefit in KIF1C -associated disease, particularly for dystonic signs.

Land use intensity, rather than plant species richness, affects the leaching risk of multiple nutrients from permanent grasslands - Valentin H. Klaus; Till Kleinebecker; Verena Busch; Markus Fischer; Norbert Hölzel; Sascha Nowak; Daniel Prati; Deborah Schäfer; Ingo Schöning; Marion Schrumpf; Ute Hamer (Global Change Biology, 2018)
The intensification of land use constitutes one of the main drivers of global change and alters nutrient fluxes on all spatial scales, causing landscape‐level eutrophication and contamination of natural resources. Changes in soil nutrient concentrations are thus indicative for crucial environmental issues associated with intensive land use. We measured concentrations of NO 3 –N, NH 4 –N, P, K, Mg, and Ca using 1,326 ion‐exchange resin bags buried in 20 cm depth beneath the main root zone in 150 temperate grasslands. Nutrient concentrations were related to land use intensity, that is, fertilization, mowing, grazing intensities, and plant diversity by structural equation modeling. Furthermore, we assessed the response of soil nutrients to mechanical sward disturbance and subsequent reseeding, a common practice for grassland renewal. Land use intensity, especially fertilization, significantly increased the concentrations of NO 3 –N, NH 4 –N, K, P, and also Mg. Besides fertilization (and tightly correlated mowing) intensity, grazing strongly increased NO 3 –N and K concentrations. Plant species richness decreased P and NO 3 –N concentrations in soil when grassland productivity of the actual year was statistically taken into account, but not when long‐term averages of productivity were used. Thus, we assume that, in the actual study year, a distinct drought period might have caused the observed decoupling of productivity from fertilization and soil nutrients. Breaking up the grassland sward drastically increased NO 3 –N concentrations (+146%) but reduced NH 4 –N, P, and K concentrations, unbalancing soil nutrient stoichiometry and boosting the risk of N leaching. Reseeding the sward after disturbance did not have a short‐term effect on nutrient concentrations. We conclude that renewal of permanent grassland should be avoided as far as possible and future grassland management has to strongly rise the effectiveness of fertilization. Additionally, grassland management might have to increasingly taking care of periods of drought, in which nutrient additions might not increase plant growth but potentially only facilitate leaching.

Official food control laboratories in Germany: results of GMO analyses from 2012 to 2016 - Hans-Ulrich Waiblinger; Ulrich Busch; Claudia Brünen-Nieweler; Geertje Denker; Sandra Döpping; Susanne Dorscheid; Christine Eichner; Norbert Graf; Peter Josefowitz; Frank-Michael Wirries; Ingo Krujatz; Dietrich Mäde; et al. (Journal of Consumer Protection and Food Safety, 2018)

The BRI-on-chip disposable test device opens up substantial savings potentials in urolithiasis treatment - Norbert Laube; Wolfgang Berg; Thomas Knoll; Heinz Busch (EPMA Journal, 2014)

The Bonn-Risk-Index for determination of the risk of urolith formation and other metabolic diseases - Norbert Laube; Wolfgang Berg; Thomas Knoll; Heinz Busch (EPMA Journal, 2014)

Hydrologische Erschließung der Bundeswasserstraße Lahn von Gießen bis zur Mündung - Dennis Meißner; Norbert Busch; Dirk Schwanenberg (WASSERWIRTSCHAFT, 2005)